Literature Review: Factors Influencing the Incidence of Multi-Drug Resistant in Tuberculosis Patients - Zahra Nur Sa'diyyah; Citra Yuliyanda Pardilawati; Oktafany, Oktafany; Asep Sukohar (Jurnal EduHealth, 2025)
Multi-Drug Resistant (MDR) tuberculosis was tuberculosis resistance to at least two first-line drugs: isoniazid and rifampicin. This resistance meant that rifampicin and isoniazid were ineffective in eradicating the Mycobacterium bacteria. The primary factor contributing to MDR TB was treatment adherence. Non-adherence led to high rates of treatment failure and was directly linked to an increase in MDR TB cases. Therefore, it is crucial to understand the contributing factors of MDR TB to prevent and reduce new occurrences. To analyze the risk factors causing MDR TB incidence in Indonesia through a literature review. The study employed a literature review method, with data obtained from Google Scholar, Research Gate, Connected Papers, and Google Books. The study found several factors that contributed to MDR TB incidence, including patient adherence, motivation, alcohol consumption, smoking, nutritional status, diabetes mellitus, history of previous treatment, the role of healthcare workers, and contact with other TB patients. The conclusion of the 13 articles reviewed shows that adherence to treatment, motivation, alcohol consumption, smoking, nutritional status, diabetes mellitus, history of treatment, role of health workers, and contact with patients were factors influencing the occurrence of MDR-TB.